Ethics briefings - Davies, Martin (Journal of medical ethics, 2012)
In November 2011, the Royal College of Obstetricians and Gynaecologists (RCOG) published its updated clinical guidelines on ‘The care of women requesting induced abortion’.1 Key changes from the previous 2004 guidelines include, among other things, that services should identify vulnerable women, for example, women being subjected to domestic abuse, and refer them on to appropriate support services; that women should be offered screening for sexually transmitted infections and there should be a system for partner notification and referral to a sexual health service; and that all appropriate methods of contraception should be discussed with women at the initial assessment and a plan agreed for contraception after the abortion.Recent debate around abortion in the UK has focused on the emotional and mental health impact of abortion. The new guidelines recommend that women should be informed about the range of emotional responses they may experience during and following an abortion, but the guidelines are clear that women with a past history of mental health problems are at increased risk of further problems after an unintended pregnancy, whether they abort or continue with a pregnancy. Other women are no more or less likely to experience adverse psychological sequelae.The RCOG's updated guidelines were swiftly followed by the Academy of Medical Royal Colleges' publication ‘Induced abortion and mental health: a systematic review of the mental health impact of induced abortion’.2 The purpose of the review was to examine the evidence of the impact of abortion upon women's mental health. The Academy's conclusions echoed the RCOG's guidelines.On the basis of the best evidence available, the review's steering group concluded that having an unwanted pregnancy is associated with an increased risk of mental health problems. The rates of mental health problems for women with an unwanted pregnancy are the same, however, whether …